The Gemini Contenders - Ludlum, Robert (Bantam Books, 1989)
Salonika, Greece; December 1939. In the dead of night, a clandestine order of monks embarks on a desperate mission: to transport a mysterious vault to a hiding place high in the Italian Alps. Its sinister contents, concealed for centuries, could rip apart the Christian world. Now, as the Nazi threat marches inexorably closer, men both good and evil will be drawn into a violent and deadly hunt, sparking a relentless struggle that could forever change the world as we know it.? Praise for Robert Ludlum and The Gemini Contenders?